Do fungivores trigger the transfer of protective metabolites from host plants to arbuscular mycorrhizal hyphae?. Issue 9 (1st September 2013) - Duhamel, Marie; Pel, Roel; Ooms, Astra; Bücking, Heike; Jansa, Jan; Ellers, Jacintha; van Straalen, Nico M.; Wouda, Tjalf; Vandenkoornhuyse, Philippe; Kiers, E. Toby
Abstract : A key objective in ecology is to understand how cooperative strategies evolve and are maintained in species networks. Here, we focus on the tri‐trophic relationship between arbuscular mycorrhizal (AM) fungi, host plants, and fungivores to ask if host plants are able to protect their mutualistic mycorrhizal partners from being grazed. Specifically, we test whether secondary metabolites are transferred from hosts to fungal partners to increase their defense against fungivores. We grew Plantago lanceolata hosts with and without mycorrhizal inoculum, and in the presence or absence of fungivorous springtails. We then measured fungivore effects on host biomass and mycorrhizal abundance (using quantitative PCR) in roots and soil. We used high‐performance liquid chromatography to measure host metabolites in roots, shoots, and hyphae, focusing on catalpol, aucubin, and verbascoside. Our most striking result was that the metabolite catalpol was consistently found in AM fungal hyphae in host plants exposed to fungivores. When fungivores were absent, catalpol was undetectable in hyphae. Our results highlight the potential for plant‐mediated protection of the mycorrhizal hyphal network.